ACCOUNTABILITY, TRANSPARENCY, COMPETENCE OF VILLAGE APPARATUS, AND INTERNAL CONTROL SYSTEM IN VILLAGE FINANCIAL MANAGEMENT - Chairin Zhela Cahyani; Yesi Mutia Basri; Pipin Kurnia (Berkala Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the effect of accountability, transparency, the competence of village officials, and internal control system on the village's financial management. The population in this study were all villages in Tandun and Ujung Batu areas, Rokan Hulu Regency. The sampling technique used in this research is saturated sampling. Saturated sampling was taken because all members of the population were used as samples. This study uses primary data through the distribution of questionnaires. Data analysis in this study used the Partial Least Square (PLS) approach with SmartPLS versionP3.0 computer software. The results of this study indicate that accountability  affects village financial management, transparency affects village financial management, villages apparatus competence affects village financial management and the internal control system affects village financial management.